FRAGMEN POLIMORFIK PENANDA RAPD UNTUK ANALISIS GENETIK SENGON (Falcataria moluccana) - Vivi Yuskianti (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2011)
This research was conducted to support tree improvement program for sengon (Falcataria moluccana (Miq.) Barneby & J.W. Grimes). Polymorphic fragments were surveyed in 288 RAPD primers using 24 materials from Okinawa, Japan. Carefully selections of the polymorphic fragments were applied to overcome a problem of low reproducibility of RAPD markers. The first screening using 4 materials found that 285 out of 288 primers successfully produced fragments. The second screening using 16 materials finally obtained 48 polymorphic fragments. High discrimination ability (DP=0.483, in average) was obtained from all the selected fragments. The selected fragments can be used to support tree improvement program of the species for genetic diversity study and to facilitate a development of more specific markers such as Sequence Characterized Amplified Region (SCAR) marker.